1998
DOI: 10.1016/s0008-6363(98)00172-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduced pulmonary metabolism of endothelin-1 in canine tachycardia-induced heart failure

Abstract: Objectives: Plasma endothelin-1 (ET-1) increases in congestive heart failure (CHF). The pulmonary vascular bed could contribute to this increase through a reduced clearance. We evaluated the effect of tachycardia-induced CHF on pulmonary ET-1 kinetics. To discern between changes due to variations in pulmonary hemodynamics from true alterations of endothelial cell functions, we quantified ET-1 kinetics in isolated rat lungs under variable pressure and flow-rate conditions. Methods and Results: Indicator-dilutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…11,12 We have previously validated the use of the PS product to evaluate pulmonary removal of tracer ET-1 and demonstrated its stability over a wide range of pulmonary blood flow, despite the expected variations in mean tracer ET extraction. 4 The PS product for ET-1 removal by the pulmonary circulation was computed as follows:…”
Section: Methodsmentioning
confidence: 99%
“…11,12 We have previously validated the use of the PS product to evaluate pulmonary removal of tracer ET-1 and demonstrated its stability over a wide range of pulmonary blood flow, despite the expected variations in mean tracer ET extraction. 4 The PS product for ET-1 removal by the pulmonary circulation was computed as follows:…”
Section: Methodsmentioning
confidence: 99%
“…The elevated ET‐1 levels in patients with heart failure result from the reduced pulmonary clearance of ET‐1. In a canine model of pacing‐induced cardiomyopathy, Dupuis et al 45 have demonstrated reductions in ET‐1 extraction in the pulmonary vascular bed due to a reduced binding affinity to the ET‐A and ET‐B receptors. Needless to say that all these various molecules and receptors could become targets for therapeutic intervention in the future.…”
Section: Abnormalities In Signaling and Neurohumoral Pathwaysmentioning
confidence: 99%
“…This reduction in pulmonary ET-1 clearance capacity has been related to endothelial ET B receptor down regulation [58], reduced receptor affinity [59] or a disturbed clearance process [60]. The functional relevance of the ET B receptor with respect to pulmonary clearance of ET-1 can be estimated following ET receptor blockade.…”
Section: Pulmonary Clearance Of Endothelinmentioning
confidence: 99%